Synthesis And Characterization Of 2, 5-Dihydroxy Substituted Chalcones Using SOCL2/ETOH - M.R.JAYAPAL; K.SREENIVASA PRASAD; N.Y.SREEDHAR (International Journal of Pharma and Bio Sciences, 2010)
A novel method for the synthesis of 2,5-dihydroxy substituted chalcones via Aldol condensation is introduced. The HCl is generated in situ by the reaction of SoCl2 with absolute ethanol. In the presence of SOCl2 / EtOH as a catalyst, The structures of the synthesized compounds were confirmed by IR, mass spectroscopy and elemental analysis.